1989
DOI: 10.1128/jb.171.5.2886-2888.1989
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of conjugal transfer of the antibiotic resistance plasmid R100 by antisense RNA

Abstract: Conjugal transfer of the normally repressed antibiotic resistance plasmid R100 was derepressed by fragments of R100 that carried the traj promoter and the traJ leader but lacked the finP promoter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Antisense RNA also regulates replication of the IncFII plasmids (Light and Molin, 1983), of plasmid RI 162 (Kim and Meyer, 1986) and of plasmid pT181 (Kumar and Novick, 1985), but in these cases regulation is exerted on the mRNAs of the replication initiation proteins. In addition, antisense RNA is involved in regulation of the hoklsok killing function of plasmid RI (Gerdes et al, 1988) and in control of the conjugal transfer of plasmids of the IncFI and IncFII groups (Dempsey, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Antisense RNA also regulates replication of the IncFII plasmids (Light and Molin, 1983), of plasmid RI 162 (Kim and Meyer, 1986) and of plasmid pT181 (Kumar and Novick, 1985), but in these cases regulation is exerted on the mRNAs of the replication initiation proteins. In addition, antisense RNA is involved in regulation of the hoklsok killing function of plasmid RI (Gerdes et al, 1988) and in control of the conjugal transfer of plasmids of the IncFI and IncFII groups (Dempsey, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the ratio of sense (traJ ) to antisense (finP ) transcripts was important in conjugal regulation (Dempsey, 1989a;1994b). Another study showed that traM transcripts had the potential to affect that ratio (Dempsey, 1994a).…”
Section: Discussionmentioning
confidence: 99%
“…The normal donor ability of R100 is 0.01-0.02 transconjugants per 100 donors (Dempsey, 1989a;1994b). Co-resident multicopy plasmids carrying finP lower that rate to 1-7 × 10 ¹4 (Dempsey, 1989a;1994b;Fee and Dempsey, 1986). Co-resident multicopy plasmids containing the traJ promoter and the traJ leader region raise the donor ability to 200 transconjugants per 100 donors (Dempsey, 1989a;1994b).…”
Section: R100 (Nr1 R222mentioning
confidence: 99%
See 1 more Smart Citation
“…Natural antisense RNAs have been shown to exert regulatory effects in bacteriophages T4 (Belin et aI., 1987), P1 and P7 (Citron and Schuster, 1990) and P22 (Liao et al, 1987), to control plasmid replication (Polisky, 1988;Persson et al, 1988;Nordstrom et al, 1988;Blomberg et al, 1990) and conjugation (Dempsey, 1989), and to regulate osmoregulatory genes (Aiba et al, 1987;'Cole and Honore, 1989) and the transposase of IS10 (Case et al, 1990;Ma and Simons, 1990).…”
Section: Antisense Control In Naturementioning
confidence: 98%